Hypergravity as a Possible Way of Bone Tissue Engineering in Osteoblastic Differentiation from Mesenchymal Stem Cells: A Systematic Review - Wisnu Sudrajad; Andre Erica Indrawan; Devangga Kusuma; Bagus Wibowo Soetojo; Heri Suroto (Journal Orthopaedi and Traumatology Surabaya)
Background: Tissue engineering development has become a highlight in recent decades. One of the key areas of focus is producing mature bone tissue to overcome orthopedic problems, such as bone defects. Various cultures have been implemented on stem cells; some induce osteoblastic differentiation markers, while others have the opposite effect. Microgravity has been proven in several studies to inhibit the expression of osteogenic differentiation markers. Conversely, hypergravity is expected to have the opposite impact, supporting stem cells in the osteogenesis pathway.